A new N-acetylgalactosamine containing peptide as a targeting vehicle for mammalian hepatocytes via asialoglycoprotein receptor endocytosis - Wu, Ying-Ta; Jiaang, Weir-Torn; Lin, Kuo-Ging; Huang, Chun-Ming; Chang, Chin-Hsien; Sun, Ying-Ling; Fan, Kuo-Hsien; Hsu, Wei-Chuan; Wang, Hsin-Ell; Lin, Shwu-Bin; Chen, Shui-Tein (Current drug delivery, 2004)
Galactoside-containing cluster ligands have high affinity for asialoglycoprotein receptors (ASGP-r), which are found in abundance in mammalian parenchymal liver cells. These ligands may be conjugated with a therapeutic drug to improve the efficiency of delivery to diseased liver cells. This report describes a new synthetic route towards clustering glycopeptides containing N-acetyl-D-galactosamine (GalNAc). The building block Fmoc-alpha-(ah-Ac3GalNAc)-L-glutamate allowed access to the target compound YEEE(alpha-ah-GalNAc)(3), a structural mimic of YEE(ah-GalNAc)(3), via solid phase peptide synthesis (SPPS). Fatty acid, poly-lysine, fluorescein and biotin conjugates further demonstrate the facility of the described method. Using fluorescein labeling and 131I labeling, in vitro and in vivo assays confirmed that YEEE(alpha-ah-GalNAc)(3) possesses both specificity and affinity to the liver, similar to the agent YEE(ah-GalNAc)(3), which targets liver lesions. The synthesis described in this report represents a considerable improvement in synthesizing a ligand for ASGP-r by simplifying both the preparation of the starting material and the procedure for conjugating the galactosidase cluster to drugs.